PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KELURAHAN DENGAN MEDIASI KOMITMEN ORGANISASIONAL (Studi Pada Pegawai Kelurahan Di Kota Pekalongan) - Rusmani Budiharjo, 12 4202 0046; Tjahjaningsih, Endang (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aimed to examine the effect of Leadership and Discipline of Work on employee performance with mediating variables of Organizational Commitment. The study was conducted at the village office se Pekalongan. The population of this study were all employees of the village in Pekalongan. Data collected through direct surveys with the help of a questionnaire given to employees of the village. Multiple linear regression analysis was used to analyze the data. Mediation effect was tested by comparing the regression coefficients of direct and indirect relationships of variables. The results showed that leadership and discipline of work and a significant positive effect on organizational commitment. Leadership, work discipline and organizational commitment and significant positive effect on employee performance. This suggests that the better leadership and discipline will be the higher employee commitment to the organization that have an impact on the higher performance of employees villages in Pekalongan. While the test showed that the mediating effect of organizational commitment did not mediate the relationship variables of leadership and discipline to employee performance village in Pekalongan. Keywords: Leadership, work discipline, organizational commitment, employee performance